Polityka władz Polski Ludowej wobec rolnictwa - Kaliński, Janusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
Immediately after the war, the agrarian policy favored individual agriculture, which was related to the attempt to neutralize the countryside in the conditions of a struggle for power and the urgent need to provide food for the population. From the end of the 1940s, ideological aspects began to dominate, emphasizing the necessity of socialization of rural areas and agriculture. As a consequence of the long-term policy towards agriculture, in which the immediate goals (improvement of the living conditions of the population) did not match the strategic ones (socialization of agriculture), agricultural production in the years 1950–1990 grew insufficiently. The problems of agriculture, generating a food shortage throughout the entire period of the People’s Poland, became an important cause of the numerous socio-political crises and the fall of the communist regime in 1989.